2001
DOI: 10.2460/javma.2001.219.941
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged anesthesia with desflurane and fentanyl in dogs during conventional and laparoscopic surgery

Abstract: Results suggest that induction of anesthesia with propofol and maintenance with desflurane and fentanyl is safe in dogs undergoing abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
8
1
2
Order By: Relevance
“…(19) yaptığı bir araştırmada propofolü köpeklere dört farklı dozda uygulamış ve yüksek dozların apneye daha çok neden olduğunu kaydetmişlerdir. İndüksiyon amacı ile uygulanan propofolün yavaş uygulandığı takdirde apneye neden olmadığını bildiren başka çalışmalar da mevcuttur (1,6,11,14,17,18,22). Bu çalışmada hiçbir hayvanda apne görülmemesi propofolün yavaş uygulanmasına ve entübasyon için yeterli derinlikte anestezi sağ-landıktan sonra uygulamanın sonlandırılmasına bağlan-mıştır.…”
Section: Tartışma Ve Sonuçunclassified
“…(19) yaptığı bir araştırmada propofolü köpeklere dört farklı dozda uygulamış ve yüksek dozların apneye daha çok neden olduğunu kaydetmişlerdir. İndüksiyon amacı ile uygulanan propofolün yavaş uygulandığı takdirde apneye neden olmadığını bildiren başka çalışmalar da mevcuttur (1,6,11,14,17,18,22). Bu çalışmada hiçbir hayvanda apne görülmemesi propofolün yavaş uygulanmasına ve entübasyon için yeterli derinlikte anestezi sağ-landıktan sonra uygulamanın sonlandırılmasına bağlan-mıştır.…”
Section: Tartışma Ve Sonuçunclassified
“…Ihre Ergebnisse zeigten regelmäßig, dass postoperativer akuter Schmerz unabhängig von der geographischen Lage oder der akademischen Ausrichtung der betreuenden Klinik nicht zufriedenstellend behandelt wird. In den vergangenen Jahrzehnten wurden daher zahlreiche nationale und internationale Initiativen zur Verbesserung der Akutschmerztherapie gestartet, Leitlinien verfasst [1,2,3,4,12,14] und wissenschaftliche Gesellschaften und Arbeitsgemeinschaften gegründet. Obwohl sich behandelnde Ärzte der besonderen Bedeutung einer effektiven postoperativen Schmerztherapie bewusst sind und heute auch weitestgehend unumstritten ist, dass eine optimierte Schmerztherapie im Rahmen definierter klinischer Behandlungspfade die Ergebnisse chirurgischer Eingriffe deutlich verbessern kann [8,10,11,22], haben wiederholte Umfragen in Deutschland [15,16,23] und anderen Nationen [18,20,21,27] keine wesentlichen Verbesserungen demonstrieren können.…”
unclassified
“…[5][6][7][8] Differences in anesthetic protocol, duration of the procedure, patient positioning, insufflation pressures, and preexisting health status have caused disparity in reported hemodynamic abnormalities during laparoscopic procedures. Cardiopulmonary effects of laparoscopy performed under general anesthesia are described for dogs, [8][9][10][11][12] horses, 13 and humans. 14,15 These studies reported increased MAP, [8][9][10]13,14 SVR, [13][14][15] and VE 9 and decreased CO, 11,13,15 arterial pH, 9,12,13,16 and Pao 2 .…”
mentioning
confidence: 99%
“…Cardiopulmonary effects of laparoscopy performed under general anesthesia are described for dogs, [8][9][10][11][12] horses, 13 and humans. 14,15 These studies reported increased MAP, [8][9][10]13,14 SVR, [13][14][15] and VE 9 and decreased CO, 11,13,15 arterial pH, 9,12,13,16 and Pao 2 . 9,13,16 Heart rate was increased in some studies 9,14 but remained unchanged in others.…”
mentioning
confidence: 99%
See 1 more Smart Citation